GML based manipulation of geodetic and mechanical data - Šljivarić, Marko (Array, 2019)
Ever since the Rulebook on cadaster of infrastructure has been published there has been constantly growing need for efficient data manipulation. However, data manipulation has been an issue for a very long period of time. This paper will provide solution in manipulation of geodetic and mechanical data for City of Zagreb gas plant. All the solutions are given in Geography markup language, GML.